Analisis Drone Emprit Kenaikan Harga BBM 2022 dalam Perspektif UU Keterbukaan Informasi Publik - Elfa Nuzila (Airlangga University, 2022)
In Indonesia, Twitter is a social media that is one of the means to find out the public's response to a policy or issue that is happening. Interactions through Twitter, such as posting tweets with specific hashtags, retweets, and likes can be known through Emprit Drone technology. Emprit drones are a technology for mapping social networks based on issues that are being discussed on Twitter. This study aims to determine the dominating public opinion towards the determination of fuel price increases and assess the role of the government in disseminating information on fuel price increases based on Law Number 14 of 2008 concerning Public Information Disclosure. The method used is a quantitative descriptive method to provide an in-depth and accurate picture. The results show that the dominating sentiment is negative sentiment which means that people tend to reject the increase in fuel prices. This negative sentiment is an indication of the government's improper behaviour in conveying information and policies to the public. Every post from Drone Emprit can be known to anyone who uses the real account and who uses the bot account. Overall, bot analysis shows Twitter accounts talking about the topic of fuel price increases have a bot score of 1,55. If the bot score is getting smaller, the number of accounts indicated as bots is getting less. Keywords: Drone Emprit, Public Information Disclosure Law, Fuel Price Increase